2019
DOI: 10.1002/mrc.4827
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of 13C NMR chemical shifts and F–C coupling constants of ciprofloxacin

Abstract: Ciprofloxacin is a widely used fluoroquinolone antibiotic. In this work, a comprehensive evaluation of MP2 and DFT with different functionals and basis sets was carried out to select the most suitable level of theory for the study of the NMR properties of ciprofloxacin. Their relative predictive capabilities were evaluated comparing the theoretically predicted and experimental spectral data. Our computational results indicated that in contrast to the solid state, the molecule of ciprofloxacin does not exist as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The first point to highlight is the high similarity between the experimental value and the theoretical value obtained for CPX in the CPX:explicit water system. The low Δδ value indicates that the method and the level of theory selected are very accurate for this type of calculation [49]. Secondly, it is observed that the value obtained in the calculation using the implicit solvation model, CPX:implicit water, is very far from the experimental value.…”
Section: Spectroscopic Parameters: 19 F-chemical Shifts (δ)mentioning
confidence: 96%
See 3 more Smart Citations
“…The first point to highlight is the high similarity between the experimental value and the theoretical value obtained for CPX in the CPX:explicit water system. The low Δδ value indicates that the method and the level of theory selected are very accurate for this type of calculation [49]. Secondly, it is observed that the value obtained in the calculation using the implicit solvation model, CPX:implicit water, is very far from the experimental value.…”
Section: Spectroscopic Parameters: 19 F-chemical Shifts (δ)mentioning
confidence: 96%
“…All 19 F NMR shielding constants calculations of this step were performed using GAUSSIAN 09 software package [59] at DFT level with the B3LYP functional and Dunning basis set [60] with diffuse function [61,62] aug-cc-pVDZ, by applying gauge-including atomic orbital (GIAO) method [63]. These levels of theory selected were based on previous parametrization studies performed on NMR calculations [64] for the CPX molecule [49]. Calculations were made for CPX in the selected frames of two MD systems using the ONIOM model [65].…”
Section: F Nmr Chemical Shift (δ) Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational methods have been widely employed to predict the spectroscopic properties of different compounds for various purposes [48][49][50]. Theoretical methods offer a fast, efficient and practical way to investigate changes in the NMR properties of different compounds, which can be caused by several factors, such as changes in the chemical environment or structure of the molecule that can occur due to interactions with biological macromolecules [29,51].…”
Section: Introductionmentioning
confidence: 99%